IMPLEMENTASI METODE GOAL PROGRAMMING UNTUK OPTIMASI OLAHAN INDUSTRI KERIPIK PISANG - Pradjaningsih, Agustina; Dwidayanti, Frisca Puji; Riski, Abduh (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
The production of chips, especially bananas, is the focus of the AROMA company in Lumajang. This business faces challenges in optimizing the use of raw materials to achieve maximum production. This challenge impacts production costs and profits, so proper production planning is needed. The goal programming method will be applied to handle this optimization problem involving various goals. This method aims to minimize deviations from each goal that has been set. The goal programming process involves identifying decision variables, goal constraints, and goal functions. The decision variables in this study included various flavors of banana chips such as chocolate, strawberry, durian, sweet, salty, chocolate-coated, and lime. Optimization problems are solved with LINDO software. The research results show that the production of banana chips can be optimized by increasing the output of lime-flavored banana chips by 200 packs. The optimization results also show total production costs of IDR 12,585,600 and profits of IDR 8,250,400.